Embodied learning and teaching approaches in language education: A mixed studies review. (November 2022) - Jusslin, Sofia; Korpinen, Kaisa; Lilja, Niina; Martin, Rose; Lehtinen-Schnabel, Johanna; Anttila, Eeva
Abstract: The notion of embodied learning has gained ground in educational sciences over the last decade and has made its way to language education with researchers acknowledging language learning as an embodied process. This mixed studies review aggregates and reviews empirical research, published from 1990 to 2020, using embodied learning approaches in language education. The review focuses on embodied approaches in learning and teaching first, second, and foreign languages at various educational levels. It encompasses 41 empirical studies with a majority published between 2019 and 2020, suggesting that the research area is growing rapidly. The results show that the studies align with two strands: (1) embodied learning through orchestrating embodied language learning and teaching, and (2) embodied learning in naturally occurring language learning interactions. The review identifies various embodied learning activities and presents how they contribute to language learning and teaching in different ways. The review proposes an understanding of embodied language learning that holds potentials to engage learners holistically, while simultaneously promoting language learning skills and adding emotional and motivational benefits to language learning. Highlights: A rapidly growing research area toward the end of the 2010s. A trend to focus on vocabulary learning with beginner learners. Possibilities to promote and add emotional and motivational benefits to language learning. Proposing an understanding of embodied language learning. Research gaps in secondary education and with intermediate and advanced language learners.